Perceptions of knowledge management and intellectual capital in the banking industry - Curado, Carla (2008)
The purpose of this article is to capture the perceptions of knowledge management and intellectual capital in the banking industry. The reason for developing such a study is that little research as clearly addressed both subjects at the same time. After verifying that knowledge management and intellectual capital are identified as different concepts in the banking industry, the final aim of the author is to identify the relevancy and perceived value of such organizational variables in the banks. In that sense, this research paper follows a qualitative approach and considers two different knowledge management strategies: exploitation and exploration and three different intellectual capital components: human capital, internal structures and external structures. The paper develops and analyses several interviews in the banking industry at top management level across different banks. This study led to some interesting findings, allowing to empirically verify most of the theoretical knowledge management and intellectual capital literatures, as well as to gather some examples of its routines and elements, and also to identify the value given to knowledge management and intellectual capital by the banks that took part of the study. There are some research limitations regarding the industry context, but this may result in a stimulus for the replication of the work in other industries. The originality of the paper regards the way it addresses simultaneously knowledge management and intellectual capital, such related concepts.